2019
DOI: 10.1088/1674-1056/ab5279
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of tungsten production from the upper divertor in EAST during edge localized modes*

Abstract: During edge localized modes (ELMs), the sheath evolution in front of the Experimental Advanced Superconducting Tokamak (EAST) upper divertor is studied to estimate the sputtered tungsten (W) atoms from the divertor target. A large potential drop across the sheath is formed during ELMs by compared with inter-ELMs, and the maximum of sheath potential drop can exceed one thousand of eV in current EAST operation. Due to the enhancement of the sheath potential drop during ELMs, the W physical sputtering yield from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The Monte Carlo simulation by Ou et al also shows similar dependence of the W physical sputtering yield on the bombardment energy and different impurity ions. [19] Thus, it is considered that the Ne seeding decreases the divertor plasma temperature to reduce the impact energy of the incident particles on the one hand, but increases the Ne impurity concentration in the divertor plasma on the other hand. The dependence of W sputtering on T et , as shown in Fig.…”
Section: Effect Of Ne Seeding On Divertor W Sputteringmentioning
confidence: 99%
“…The Monte Carlo simulation by Ou et al also shows similar dependence of the W physical sputtering yield on the bombardment energy and different impurity ions. [19] Thus, it is considered that the Ne seeding decreases the divertor plasma temperature to reduce the impact energy of the incident particles on the one hand, but increases the Ne impurity concentration in the divertor plasma on the other hand. The dependence of W sputtering on T et , as shown in Fig.…”
Section: Effect Of Ne Seeding On Divertor W Sputteringmentioning
confidence: 99%
“…The sputtered C atoms would bombard the W divertor and aggravate the sputtering behavior of W. It is concluded that the low-Z impurities in the D main plasma, such as carbon and beryllium, would cause the sputtering of W divertor plate in the divertor region, rather than pure D incident flow. In the plasma discharge vessel of EAST, the internal parts of carbon-based materials would be bombarded by the edge plasma and generated hydrocarbons, which would influence the W sputtering behavior [29]. It should be noted that the chemical sputtering yield of C usually accounts for only 1% [30], and physical sputtering is mainly considered and discussed, here.…”
Section: Impact Of Carbon Impurity On Tungsten Sputteringmentioning
confidence: 99%
“…Tungsten has been considered as one of the candidate PFMs for ITER because of its favorable physical and chemical properties, such as high thermal conductivity, high melting point, high-temperature mechanics performance, low physical and chemical sputtering yields, and no chemical reaction with hydrogen. [1][2][3][4][5][6][7] However, the brittleness of W material leads PFM to likely undergo crack failure when the transient event occurs. [8] W-Y 2 O 3 alloys can effectively impede the recovery and recrystallization at high temperature, and have low ductilebrittle transition temperature (DBTT) compared with pure tungsten.…”
Section: Introductionmentioning
confidence: 99%